471 Identifying gaps in evaluation, treatment, and treatment adherence in women Veterans with sleep disordered breathing risk factors. (3rd May 2021) - Moghtaderi, Isabel; Kelly, Monica; Carlson, Gwendolyn; Swistun, Dominika; Fung, Constance; Zeidler, Michelle; Mitchell, Michael; Josephson, Karen; Lee, Diane; Partch, Lisa; Badr, Safwan; Washington, Donna; et al.
Abstract: Introduction: In our recent national survey study, 13% of women Veterans reported a diagnosis of Sleep Disordered Breathing (SDB), of whom 65% used positive airway pressure (PAP) treatment. We also found many women Veterans at high risk for SDB were undiagnosed (43%). The current study builds upon this survey research to identify rates of evaluation, diagnosis, treatment, and treatment adherence among women Veterans with risk factors for SDB. Methods: We analyzed telephone screening data from an ongoing SDB treatment adherence intervention study for women Veterans in Los Angeles county. A total of 173 women Veterans, identified by retrospective chart review as having at least one risk factor for SDB (i.e. high blood pressure, diabetes, obesity, depression, or > 50 years old), completed the screener. Screening questions included 1) previous diagnostic testing for SDB, 2) SDB diagnosis 3) SDB treatment type, and 4) past week SDB treatment use. Descriptive statistics regarding evaluation and treatment of SDB are reported. Results: In total, 31% of respondents endorsed having previously completed diagnostic testing, of whom, 54% reported an SDB diagnosis. Of those with diagnosed SDB, 82.8% were prescribed treatment (PAP [72.4%], oral appliance [6.9%], surgery [3.5%]), and 17.2% did not report being prescribed any SDB treatment. Of the 21 (72.4%) women Veterans diagnosed with SDB that were prescribed PAP, only 33% reported using treatment in the past week. Of the 2 women Veterans (6.9%) prescribed an oral appliance, 0% reported past week use. Conclusion: Less than 1/3 of women Veterans with at least one risk factor for SDB had previously been evaluated for SDB; however, over 1/2 of women Veterans who were evaluated tested positive for SDB. Additionally, most women Veterans had not used PAP or oral appliance therapy in the past week. Greater clinical attention is needed to identify, evaluate, and diagnose SDB in women Veterans. Moreover, further research is needed to evaluate and inform interventions to address SDB treatment adherence barriers in women Veterans. Support (if any): VA HSR&D IIR 16–244 and RCS 20–191; NIH/NHLBI K24 HL143055, VAGLAHS GRECC and VA Office of Academic Affiliations.